Frequency of thunderstorms in South India - WILLIAMS, S. D. (MAUSAM, 1961)
In this paper the average frequency of days of thunder in the different states of South India based on data for the years 1946 to 1956 have been discussed. Kerala State has the highest annual frequency of 57 while Madras has 37 and Mysore and Andhra Pradesh 29 each. In Madras State, there is a marked decrease of thunderstorm frequency along the coastal regions compared to the interior and this is very pronounced as one goes south.